Monitoring and evaluating the ecological integrity of forest ecosystems. Issue 6 (28th January 2009) - Tierney, Geraldine L; Faber-Langendoen, Don; Mitchell, Brian R; Shriver, W Gregory; Gibbs, James P
Abstract : "Ecological integrity" provides a useful framework for ecologically based monitoring and can provide valuable information for assessing ecosystem condition and management effectiveness. Building on the related concepts of biological integrity and ecological health, ecological integrity is a measure of the composition, structure, and function of an ecosystem in relation to the system's natural or historical range of variation, as well as perturbations caused by natural or anthropogenic agents of change. We have developed a protocol to evaluate the ecological integrity of temperate zone, forested ecosystems, based on long‐term monitoring data. To do so, we identified metrics of status and trend in structure, composition, and function of forests impacted by multiple agents of change. We used data, models, and the scientific literature to interpret and report integrity using "stoplight" symbology, ie "Good" (green), "Caution" (yellow), or "Significant Concern" (red). Preliminary data indicate that forested ecosystems in Acadia National Park have retained ecological integrity across a variety of metrics, but that some aspects of soil chemistry and stand structure indicate potential problems. This protocol was developed for the National Park Service Vital Signs Monitoring Program and holds promise for application in the temperate zone, forested ecosystems of eastern North America.